2023
DOI: 10.3390/app13106185
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Acid- and Enzyme-Induced Coagulation of Raw Milk Using Dielectric and Rheological Measurements

Abstract: In this study, the enzyme-induced and acid coagulation of raw milk samples were investigated, and these two processes were monitored by determining the changes in dielectric and rheological behavior to see if any correlations could be found between these two properties. For the enzyme-induced experiments, 250 cm3 of raw milk sample and industrial chymosin were used, and during the acid coagulation, industrial thermophile yogurt culture was added to the same amount of milk. The apparent viscosity was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…The results of this research led to the conclusion that the dielectric constant at 1.5 kHz was correlated with the state of spoilage of different frozen fish, while the conductivity of the test materials varied independently of spoilage [9]. In one of our earlier studies we have shown that dielectric analysis can also be used during the coagulation of raw milk: strong correlation was found between the apparent viscosity and the dielectric constant of the milk samples during the acid-and enzyme-induced coagulation of the samples [10]. The results of these earlier studies have also shown that, although the suitability of dielectric measurement as an indirect but rapid method for indicating changes in the deterioration phenomena of foodstuffs or food raw materials (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…The results of this research led to the conclusion that the dielectric constant at 1.5 kHz was correlated with the state of spoilage of different frozen fish, while the conductivity of the test materials varied independently of spoilage [9]. In one of our earlier studies we have shown that dielectric analysis can also be used during the coagulation of raw milk: strong correlation was found between the apparent viscosity and the dielectric constant of the milk samples during the acid-and enzyme-induced coagulation of the samples [10]. The results of these earlier studies have also shown that, although the suitability of dielectric measurement as an indirect but rapid method for indicating changes in the deterioration phenomena of foodstuffs or food raw materials (e.g.…”
Section: Introductionmentioning
confidence: 90%